Biodegradation of tricresyl phosphate isomers by Brevibacillus brevis: Degradation pathway and metabolic mechanism. (October 2019) - Liu, Ying; Yin, Hua; Wei, Kun; Peng, Hui; Lu, Guining; Dang, Zhi
Abstract: Tricresyl phosphates (TCPs), a typical sort of organophosphate flame retardants, has received extensive concerns due to its potential adverse effects. However, limited information is available on the efficient and safe removal methods of TCPs. In this regard, TCPs were tentatively biodegraded with Brevibacillus brevis . A probable degradation pathway was further proposed with the cellular reactions discussed in detail. Experiments showed that B. brevis at 2 g L −1 could degrade 1 mg L −1 tri-m-cresyl phosphate, tri-p-cresyl phosphate, and tri-o-cresyl phosphate by 82.91%, 93.91%, and 53.92%, respectively, within five days. In the process of biodegradation, B. brevis metabolism caused the release of Na + and Cl − as well as the absorption of some nutrient ions including K +, PO4 3−, Mg 2+, and SO4 2− ; the presence of oxalic acid, citric acid, acetic acid, and malonic acid was also detected. Similar metabolic pathways were found among different TCPs isomers, but tri-o-cresyl phosphate induced more reactive oxygen species than the other two did. This work develops novel insights into the potential mechanisms of TCPs biodegradation by microorganisms. Graphical abstract: Image 1 Highlights: B. brevis could degrade TpCP and TmCP more effectively than ToCP. Biodegradation pathways were speculated based on the metabolites of TCP isomers. Organic acids produced by B. brevis were detected during the degradation process. TCP isomers induced oxidative stress on B. brevis.